2021
DOI: 10.1038/s41598-021-95670-8
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene related peptide α is dispensable for many danger-related motivational responses

Abstract: Calcitonin gene related peptide (CGRP) expressing neurons in the parabrachial nucleus have been shown to encode danger. Through projections to the amygdala and other forebrain structures, they regulate food intake and trigger adaptive behaviors in response to threats like inflammation, intoxication, tumors and pain. Despite the fact that this danger-encoding neuronal population has been defined based on its CGRP expression, it is not clear if CGRP is critical for its function. It is also not clear if CGRP in o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Both the Calca and Calcb genes encode calcitonin gene-related peptide (CGRP), but Calcb is only weakly expressed based on scRNA-Seq, which is consistent with the observation that Calca -null mice express negligible CGRP immunofluorescence in the PBN ( Allen et al, 2022 ; Chen et al, 2018 ; Zajdel et al, 2021 ). The AMBA shows robust expression of Calcb perhaps because their probe hybridized to both genes.…”
Section: Resultssupporting
confidence: 79%
“…Both the Calca and Calcb genes encode calcitonin gene-related peptide (CGRP), but Calcb is only weakly expressed based on scRNA-Seq, which is consistent with the observation that Calca -null mice express negligible CGRP immunofluorescence in the PBN ( Allen et al, 2022 ; Chen et al, 2018 ; Zajdel et al, 2021 ). The AMBA shows robust expression of Calcb perhaps because their probe hybridized to both genes.…”
Section: Resultssupporting
confidence: 79%
“…2H). In line with previous findings demonstrating that the Calca gene is dispensable for acute pain sensation (Zajdel et al, 2021), these data indicate that, while activation of PBN Calca neurons is sufficient to drive nociplasticity, the Calca gene product, CGRP, does not play a role in this assay. However, it is worth noting that CGRP is important in arthritis-, formalin-, and bladder-pain models (Allen et al, 2023; Shinohara et al, 2017; Han et al, 2015).…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have shown that CeA-projecting PbN neurons do not receive direct nociceptive inputs from the spinal cord (7, 36, 37). Separate studies have demonstrated that the PbN is activated in response to peripheral noxious stimulation (12, 13, 38, 39) and that injury potentiates the PbN→CeA pathway in several mouse models of persistent pain. Whether CeA-projecting PbN neurons are activated by peripheral noxious stimulation remains unknown.…”
Section: Resultsmentioning
confidence: 99%